Infrastructure planning emergency levels of service for the Wellington region, Aotearoa New Zealand : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology (Emergency Management) at Massey University, Wellington, New Zealand - Mowll, Richard (Massey University, 2024)
Past work has demonstrated that the infrastructure in the Wellington region, Aotearoa New Zealand, is vulnerable to natural hazard events such as earthquake and tsunami. To enable common understandings of the levels of service (or targets) that critical infrastructure entities are planning on delivering in an emergency event, the concept of ‘planning emergency levels of service’ (PELOS) is developed and presented in this thesis. Such a concept is readily relatable to the water sector where, for example, the World Health Organisation’s ‘basic access’ to water standard is for ’20 litres of water, per person, per day, within 1km of the dwelling’. Despite such standards for water, there are few other examples in the sectors of energy, telecommunications and transport. A literature review investigated relevant sources of information on the concept from both academic and from infrastructure sector-specific texts and was used in developing a preliminary framework of PELOS, alongside discussions with emergency management experts in the Wellington region. The overall PELOS concept and preliminary framework was then presented in interviews and workshops with key stakeholders, and qualitative data collected from these interactions was used to create an ‘operationalised’ PELOS framework. This framework was adopted by the Wellington Lifelines Group, a grouping of the critical infrastructure entities in the region. Key themes of the PELOS concept are explored, namely: interdependencies, the need to consider the vulnerabilities of some community members, emergency planning considerations, stakeholders’ willingness to collaborate and the flexibility/adaptability of the delivery of infrastructure services following a major event. Further, a description of the process taken to develop the framework is provided to enable other regions to create their own frameworks. A mapping tool, visualising where PELOS can, and cannot, be achieved based on hazard impact modelling is presented. This allows the infrastructure entities, the impacted communities and the emergency management sector to have a common understanding of the targets of response following a major hazard event, and plan for them in future.
Keywords: Emergency management; Planning; Disaster victims; Services for; New Zealand; Wellington; Infrastructure (Economics); Earthquake effects; Disasters; Psychological aspects; 350703 Disaster and emergency management